Simulation of Wiped Film Evaporator - A. Al-Hemiri, Adil; F. Mansour, Emad; A.L. Al-Ani, Jamal (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
A mathematical model and associated computer program were developed to simulate the steady state operation of wiped film evaporators for the concentration of glycerol-water solution. In this model, various assumptions were made to facilitate the mathematical model of the wiped film evaporator. The fundamental phenomena described were: sensible heating of the solution and vaporization of water. Physical property data were coded into the computer program, which performs the calculations of this model. Randomly selected experiments were carried out in a small scale wiped film evaporator from ALVAL COMPANY, using different concentrations of the glycerol solution (10, 30 and 50 Wt. %) for different feed rates (30, 50, 80, 100 and 120 l/h) and two values of steam jacket pressure (2 and 4 atm) to compare between experimental and simulation results. The statistical analysis gave correlation coefficient of 0.9972, average absolute error of 2.2527 % and F-test of 0.9639 which showed the high accuracy of the simulation work.